Efisiensi Ekonomi Pemeliharaan Ayam Kampung Super yang Diberi Fitobiotik dengan Teknologi Nanoenkapsulasi Minyak Buah Merah (Pandanus conoideus) - Maria Herawati; Bangkit Lutfiaji Syaefullah; Ni Putu Vidia Tiara Timur (Wahana Peternakan, 2020)
Red fruid as one of Indonesia’s native medicinal plants as a phytobiotic is developed to maintain the health status of livestock. The drawback of using phytobiotics as feed additives is done by making nanoencapsulation so that the products are easily absorbed by the livestock digestive system. This research was conducted to know the value of the economic efficiency using red fruit oil nanoencapsulation in super native chickens. The study used a descriptive method with 5 treatments and 4 replication. P0 (control), P1 (2.5% red fruit oil extract), P2 (2.5% red fruit oil nanoencapsulation), P3 (5% red fruit oil nanoencapsulation), P4 (10% red fruit oil nanoencapsulation). The result showed that the economic efficiency of using feed in each treatment was efficient (EEPP<1) dan the best business efficiency (R/C) in P2 treatment (1,474). The conclusion of this study is that the use of red fruit oil nanoencapsulation in super native chicken can provide a better economic efficiency value than those without nanoencapsulation. The use of 2.5% red fruit oil nanoencapsulation gave the best economic efficiency value compared to other treatments.